Implementasi Pendaftaran Hak Atas Tanah Komunal di Desa Adat Pakraman Bungbungan Bali - Adnyani, Ni Putu; Kuswahyono, Imam; Supriyadi, Supriyadi (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2020)
This study aimed to analyze the application of the registration of communal land rights of indigenous and tribal peoples in the Pakraman Bungbungan Traditional Village, Jembrana Regency, as well as to explore issues that hampered registration of communal land rights and efforts made by the government to overcome these obstacles. The study method used an empirical legal study with a sociological juridical approach. From the study results, it was known that the registration of communal land rights in the Desa Adat Pakraman Bungbungan, Jembrana Regency, Bali Province was implemented through the Government’s Strategic Program, namely the Complete Systematic Land Registration 2019. There were several obstacles experienced, one of them being the community’s ignorance of the communal land registration process. The effort made by officials of the Jembrana District Land Office was to disseminate information to indigenous peoples regarding the way to register communal land.